Trajetórias de mudança dos predicados acabar, acontecer e começar sob perspectiva discursivo-funcional - Silva-Surer, Tatiana Mazza da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study aimed to investigate the multifunctionality of the predicates acabar, acontecer and começar, in the history of Brazilian Portuguese, assuming as a theoretical framework two theories of linguistic change - Lexicalization and Grammaticalization - in interaction with the study of Functional Discourse Grammar (HENGEVELD & MACKENZIE, 2008). Lexicalization is considered here as the process through which single items or constructions become part of the language lexicon with a new specific meaning (LEHMANN, 2002a), while Grammaticalization is regarded as the process which leads items or lexical constructions to acquire, in specific contexts, grammatical functions or, if those items have already undergone grammaticalization, to continue and develop new grammatical functions. The latter process covers, throughout its development, a rising level of pragmatization of meaning and recategorization of the items and constructions involved (HOPPER & TRAUGOTT, 2003). In accordance to the model of description proposed by the theory of Functional Discourse Grammar, our hypothesis predicted that the trajectory of change perceived in the analyzed predicates would respect the hierarchical order of the layers and the levels of the grammatical representation. Empirical investigation was conducted on corpora composed of: (i) historical written texts of various discourse genres from the 18th to the 21st century; and (ii) Modern Brazilian Portuguese spoken data from the 20th to the 21st century. The results of the corpora investigation led to the findings of seven different patterns of use for the predicate acabar, two different patterns of use for the predicate acontecer and four different patterns of use for the predicate começar. We were also able to establish that all predicates converged, in their respective trajectories of change, to the same pattern of use: that of an argumentative operator...

Nosso objetivo nesta tese é analisar a multifuncionalidade dos predicados acabar, acontecer e começar, na história do português brasileiro, assumindo como quadro teórico duas teorias de mudança linguística - Lexicalização e Gramaticalização - na interface com a Gramática Discursivo-funcional (HENGEVELD e MACKENZIE, 2008). Lexicalização caracteriza-se como processo por meio do qual itens ou construções entram para o léxico da língua com um significado específico (LEHMANN, 2002a), e Gramaticalização, como processo que leva itens ou construções lexicais a assumirem, em contextos específicos, funções gramaticais ou, se já gramaticalizados, a continuar a desenvolver novas funções gramaticais, envolvendo, no decorrer do processo, pragmatização crescente de sentidos e recategorização dos itens ou construções (HOPPER & TRAUGOTT, 2003). Em acordo com modelo de descrição proposto pela Gramática Discursivo-funcional, assumimos como hipótese que a trajetória de mudança percorrida pelos predicados em análise respeita a ordem hierárquica das camadas e dos níveis de representação gramatical. A investigação empírica toma por base corpora compostos de textos históricos do português brasileiro de diferentes gêneros do discurso dos séculos XVIII ao XXI e também de dados de fala do português brasileiro contemporâneo dos séculos XX e XXI. Como resultado da pesquisa em corpora, levantamos para o predicado acabar sete diferentes padrões de uso, para acontecer, dois diferentes padrões de uso, e para começar, quatro padrões de uso, e mostramos que todos os predicados convergem, em suas respectivas trajetórias de mudança, para o mesmo padrão de uso como operador argumentativo. Essa constatação nos permitiu propor um percurso de mudança envolvendo os diferentes padrões de usos de cada um dos predicados, o qual, na arquitetura da Gramática Discursivo-funcional...
Keywords: Linguística; Servidores públicos; Semantica